Phosphodiesterase 4 Inhibitors in Allergic Rhinitis/Rhinosinusitis - Janosova, Viera; Calkovsky, Vladimir; Pedan, Heiko; Behanova, Estera; Hajtman, Andrej; Calkovska, Andrea (Frontiers in Pharmacology, 2020)
Allergic rhinitis/rhinosinusitis (AR) is the most common allergic disease. It affects patients’ quality of life and may influence the severity of lower airway disease such as asthma. Therefore, its treatment is of great importance. AR is treated by a combination of effective approaches; however, in some patients, the disease is uncontrolled. In the last several years, the concept of AR has shifted from increased T helper 2 (Th2) cell signaling and downstream inflammation to disease phenotypes with non-Th2-mediated inflammation. AR is a largely heterogenous group of airway diseases, and as such, research should not only focus on immunosuppressive agents (e.g., corticosteroids) but should also include targeted immunomodulatory pathways. Here, we provide an overview of novel therapies, focusing on the role of phosphodiesterase-4 (PDE4) inhibitors in AR. PDE4 inhibitors are potent anti-inflammatory agents that are used for the treatment of inflammatory airway diseases including AR. The PDE4 inhibitor roflumilast was shown to effectively control symptoms of AR in a randomized, placebo-controlled, double-blinded, crossover study in patients with a history of AR. However, only a few PDE4 inhibitors have proceeded to phase II and III clinical trials, due to insufficient clinical efficacy and adverse effects. Research is ongoing to develop more effective compounds with fewer side effects that target specific inflammatory pathways in disease pathogenesis and can provide more consistent benefit to patients with upper airway allergic diseases. Novel specific PDE4 inhibitors seem to fulfill these criteria.